Novel Indices to Improve the Diagnostic Ability of Nocturnal Oximetry in Children with OSAS - Panagiota Pappa; Konstantinos Kourelis; Anastasios Goulioumis; Magdalene Tsiakou; Panagiotis Plotas; Aris Bertzouanis; Ilias Theodorakopoulos; Konstantinos Mourtzouchos; Michael B. Anthracopoulos; Athanasios Asimakopoulos; Sotirios Fouzas (MDPI AG, 2023)
Nocturnal pulse oximetry (NOx) is an alternative diagnostic test for obstructive sleep apnea syndrome (OSAS) in childhood yet with variable diagnostic performance. Our aim was to apply advanced signal analysis to develop novel and more accurate NOx indices. We studied 45 children aged 3-10 years who underwent adenotonsillectomy for adenotonsillar hypertrophy and OSAS symptoms. Participants performed NOx before and three months after surgery, and the changes in McGill oximetry score (MOS), oxygen desaturation ≥3% index (ODI3), and the novel parameters-cumulative saturation area (CSA) and oxygen saturation sample entropy (SSE)-were assessed. There was a significant improvement (p < 0.001) in all NOx indices. When pre- and post-adenotonsillectomy NOx recordings were compared, the MOS had an area under the curve (AUC) of 0.811 with 63.2% sensitivity and 100% specificity at a cutoff >1. The AUC of ODI3 was 0.994, with 97.8% sensitivity and 91.1% specificity at a cutoff of >3.6 events per hour. The CSA and SSE had an AUC of 1.00, with 100% sensitivity and specificity at a cutoff of >293 and >0.99, respectively. We conclude that the herein-introduced indices-CSA and SSE-hold promise in improving the diagnostic ability of NOx in children suspected of OSAS.